Proceedings of the 2016 ACM Conference on Designing Interactive Systems 2016
DOI: 10.1145/2901790.2901795
|View full text |Cite
|
Sign up to set email alerts
|

Phases of Urban Tourists' Exploratory Navigation

Abstract: There is a lack of widely available mobile map applications that effectively support pedestrian tourists who prefer the freedom of exploring their surroundings, and might not have an explicit destination they are trying to reach in mind. Although research systems to support such exploratory navigation have been developed, these are often only studied in controlled trials. It is therefore unclear if researchers are covering all types of navigation tourists do. To get a comprehensive picture of tourists' navigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
1
13
0
4
Order By: Relevance
“…Similarly, in tourists' exploratory travel the decision to leave an area requires considering the effort needed to find more interesting places from the current area, the effort to move to a new area, and the expected interestingness of the new the area. In our previous study, we observed tourists' exploration and saw that, when the time was limited and area large, people started to weight the gains of exploring the city further against the effort of having to rush to their next engagement, exactly as foraging theory predicts [5]. As in the case of information search, foraging theory could be used to inform the design of the tools for exploratory travel, but so far examples of this are missing from the literature.…”
Section: Foraging Theorymentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, in tourists' exploratory travel the decision to leave an area requires considering the effort needed to find more interesting places from the current area, the effort to move to a new area, and the expected interestingness of the new the area. In our previous study, we observed tourists' exploration and saw that, when the time was limited and area large, people started to weight the gains of exploring the city further against the effort of having to rush to their next engagement, exactly as foraging theory predicts [5]. As in the case of information search, foraging theory could be used to inform the design of the tools for exploratory travel, but so far examples of this are missing from the literature.…”
Section: Foraging Theorymentioning
confidence: 97%
“…However, Brown [3] and Brown et al [4] discovered that tourists often do not want to create explicit route plans, but rather head in the roughly correct direction and make detours at will. Furthermore, previous work found that tourists switch fluidly between traveling to novel destinations and exploratory travel, reacting dynamically to the opportunities they see around them [5]. For them, reaching a specific destination is usually not the ultimate goal of their wayfinding.…”
Section: Introductionmentioning
confidence: 99%
“…Hyvä saavutettavuus ei kuitenkaan tarkoita liikkuvuuden toteutumista (Yu 2016;Kuisma 2017, 14-15). Tutkimusten mukaan kielitaidottomuus voi olla yksi este maahanmuuttajien liikkuvuudelle (Chang 2013(Chang , 2015Johnson & Miles 2014;Vaittinen & McGookin 2016). Heikko kielitaito ja sen aiheuttama pelko liikkua ennestään tuntemattomille alueille tai käyttää uusia kulkuvälineitä tai joukkoliikennelinjoja vähentävät maahanmuuttajien liikkuvuutta (Chang 2013;2015) ja estävät heitä nauttimasta samoista resursseista ja palveluista kuin kyseisen maan kieltä osaavat kaupunkitilan käyttäjät.…”
Section: Kaupunkitilan Kokeminen Ja Tilan Saavutettavuusunclassified
“…Useissa tutkimuksissa onkin painotettu symbolikielen lisäämistä kaupunkiympäristöihin saavutettavuuden ja kielellisen esteettömyyden parantamiseksi (esim. Chang 2015; Vaittinen & McGookin 2016).…”
Section: Liikkuminen Kaupunkiympäristössä Ja Kielimaiseman Vaikutus Nunclassified
See 1 more Smart Citation